Censorship detected in EG (Egypt) - Voidly (2026)
CRITICAL severity censorship detected in Egypt. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: EG-2026-1575
Keywords: censorship; EG; censorship; critical